PENGARUH PENERAPAN STRATEGI PEMBELAJARAAN AKTIF TIPE STARTS WITH A QUESTION (LSQ)TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 25 PADANG (JURNAL LEMMA, 2019)
This research is conducted because of low mathematics learning achievement phenomenon. It is also aimed to know whether Learning Start with a Question (LSQ) learning will give better effect toward students’ learning achievement than conventional learning strategy at grade VIII students of SMPN 25 Padang. Thus, this research is an experimental research. The population of this research is all of grade VIII students of SMPN 25 Padang. The sample is then chosen randomly with the result of grade VIII3 as experimental class and VIII4 as control class. The instrument of this research is a test with 0,845 of reliability. The hypothesis is tested by using one-tailed t test. The result of data analysis shows that both of two classes samples have normal distribution and homogeneous variance. Based on the result of hypothesis analysis, it can be concluded that the result of students'mathematics learning achievement after applying the active learning model of Learning Starts with a Question (LSQ) is almost the same with students' mathematics learning achievement of conventional learning strategyin grade VIII of SMP 25 Padang.